Determination of deoxyhemoglobin S polymer in sickle erythrocytes upon deoxygenation. - Noguchi, C T (1980)
We have used 13C/1H magnetic double-resonance spectroscopy to measure the amount of sickle hemoglobin polymer within sickle erythrocytes as a function of oxygen saturation. We previously showed that the methods of cross-polarization and scalar decoupling could be used to measure accurately the polymer fraction in deoxygenated sickle hemoglobin solutions [Noguchi, C.T., Torchia, D.A. & Schechter, A.N. (1979) Proc. Natl. Acad. Sci. USA 76, 4936-4940]. Our measurements show that the amount of intracellular deoxyhemoglobin S polymer increases monotonically with decreasing oxygen saturation. Polymer can be detected at oxygen saturation values above 90%. This result can be theoretically explained by the excluded volume effect of the oxyhemoglobin S in the cell. The very high total intracellular hemoglobin concentration (34 g/dl) reduces the amount of soluble deoxyhemoglobin S to about 3 g/dl at 90% oxygen saturation. The agreement between theory and experiment indicates that the equilibrium properties of intracellular polymerization can be described by the analyses resulting from studies of concentrated sickle hemoglobin solutions. The curve for polymer formation as a function of oxygen saturation is roughly hyperbolic whereas that for cell sickling is sigmoidal; the difference is most apparent for measurements at pH 7.65. Intracellular polymer formation may in general have a different relationship to oxygen saturation than cell sickling and may be a more meaningful parameter of the pathophysiological process in sickle cell anemia than cell morphology. In addition, measurements of intracellular polymer should be useful in evaluating potential therapeutic agents.